From syllabus design to curriculum development - Mariana Ulfah Hoesny (Jurnal Linguistik Terapan, 2013)
Syllabus and curriculum are known as two aspects of instructional activities. Syllabus is can be defined as an outline and summary of topics that has to be covered in an education or training course. The syllabus sets the onward responsibilities of teacher to the students. Teachers can develop syllabus based on the curriculum. Curriculum itself is a broad notion covering the whole body of knowledge the students shall acquire in the school and general description of the teaching program. In short, curriculum is the general statement about the teaching program and syllabus is the about what actually happens in the classroom. Further, this article also presents kinds, components and functions of syllabus and how curriculum is developed. It also discusses about some problems encountered in the implementation of syllabus and curriculum.